Social media for academics : a practical guide - Pennington, Diane Rasmussen (Chandos social media series., 2012)
This book provides an overview of social media technologies in the context of practical implementation for academics, guided by applied research findings, current best practices, and the author's successful experiences with using social media in academic settings. It also provides academics with sensible and easy strategies for implementing a wide spectrum of social media and related technologies - such as blogs, wikis, Facebook, and various Google tools for professional, teaching, and research endeavours. No other book exists that assists academics in learning how to use social media to benefit their teaching and researchThe editor has an extensive background in social media teaching, consulting, research, and everyday useAll the contributors come to the book with a common goal, from various expertise areas and perspectives.